Peningkatan Kemampuan Guru dalam Menulis RPP dan Presentasi melalui Supervisi Kepala Sekolah di Sekolah Dasar - Yulianti, Defitri; Nurmalina, Nurmalina; Masrul, Masrul (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
Principal supervision is one of the duties and functions that must be carried out by school principals in the school environment which are their duties and responsibilities. One of the supervisions carried out by the principal is to maintain and ensure the competence of teachers remains qualified. This study aims to improve the ability of teachers in writing lesson plans and presentations through supervision by the principal. The method used in this research is the school action research method. This method has four stages, namely planning, implementation, observation, and reflection. The research subjects were 18 teachers consisting of 3 male teachers and 15 female teachers. Data collection techniques used are observation and documentation. The research instrument used was the teacher's lesson plan assessment sheet and the teacher's presentation observation sheet. The results of the study can increase the ability to write lesson plans and teacher presentations from pre-action to cycle 1 by 10,2%. Therefore, this research can be used as a reference in improving the ability to write lesson plans and teacher presentations as a whole by 10,2%. Supervision of school principals needs to be carried out continuously so that teacher competence is maintained.